An Employment of Images and Typography as a Means of Communication on Book Covers - Abbas Faisal Mushtat ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study aims to examine the employment of images and typography as means of communication on book covers by analyzing their visual and semantic relationships and their role in shaping a book’s visual identity and attracting readers. The research explores the historical background of book cover development and the importance of graphic design in their creation. It also discusses the types of images, the functions of typography, and their contributions to reinforcing the visual message and achieving harmony between form and content. Furthermore, the study reviews leading international design standards applied in book cover design and their impact on shaping the reader’s experience and influencing purchasing behavior.The findings indicate that the deliberate integration of images and typography enhances the aesthetic and marketing value of book covers, strengthens communication with the target audience, and encourages reader engagement with the book. Consequently, this integration fulfills aesthetic, communicative, and promotional functions simultaneously. The study concludes that adopting a design vision that considers both cultural context and contemporary aesthetic standards is essential for achieving more effective and impactful book covers.DOI: https://doi.org/10.54633/2333-024-056-023